PP65 What is the Effect of a Behaviour Change Intervention on the Diets and Physical Activity Levels of Women Attending Sure Start Children's Centres in Southampton? Findings from a Non-Randomised Controlled Trial. (10th September 2013) - Baird, J; Jarman, M; Lawrence, W; Black, C; Davies, J; Tinati, T; Begum, R; Mortimore, A; Robinson, S; Margetts, B; Cooper, C; Barker, M; et al.
Abstract : Background: A major component of the government response to the obesity epidemic includes action in communities to improve people's health behaviour. This study evaluated the effects of a community-based intervention on dietary quality and physical activity of women from disadvantaged backgrounds. The intervention consisted of training Sure Start Children's Centre (SSCC) staff in skills to support behaviour change. Methods: We conducted a non-randomised controlled trial with mixed methods process evaluation. Participants were 527 women attending Sure Start Children's Centres in Southampton (intervention area) and 495 women attending Centres in Gosport and Havant (control area). Main outcomes were dietary quality, physical activity, self-efficacy and sense of control assessed before and one year after the intervention. Intervention and control group outcomes were compared using linear regression and adjusting for level of the corresponding variable at baseline. Results: Process evaluation showed that intervention staff used skills to support behaviour change significantly more than control staff (p < 0.001) one year post-training. There were, however, significant reductions of 0.1 SD in women's dietary quality, 0.06 SD in self-efficacy and 0.18 SD in sense of control in both the intervention and control groups between baseline and follow up. There were no significant differences between the intervention and control groups in the magnitude of change in dietary quality. We found, however, that the magnitude of decline in self-efficacy and control was significantly smaller in the intervention women than in women from the control areas. There was a statistically significant improvement in physical activity level between baseline and follow up in the intervention group; 22.9% of women reported the highest level of physical activity at follow up compared with 12.4% at baseline. There was a smaller improvement in physical activity in the control group that was not statistically significant. However, the difference in magnitude of change in physical activity level between the groups was not statistically significant. Conclusion: The intervention led to sustained increase in skills to support behaviour change among SSCC staff, but did not result in improvement in the dietary quality and physical activity of intervention group women compared with controls. There was, however, a protective effect on women's self-efficacy and sense of control (factors known to be associated with dietary quality). These findings suggest that more prolonged exposure to the intervention may lead to improvements in health behaviour and, given the challenges of evaluation in a community setting, that further evaluation in a more controlled setting is justified.